Multi-atomic catalysts: Pioneering applications in the pursuit of carbon neutrality - Jiarui Yang; Dingsheng Wang (Carbon Future)
Since the introduction of single-atom catalysts (SACs), they have attracted considerable attention. Their high atomic efficiency and simple coordination environment make SACs a promising alternative to commercial catalysts. However, they face limitations, often showing relatively low efficiency in producing multi-carbon products. In contrast, multi-atomic catalysts (MACs), with their higher exposure of active sites, may outperform SACs owing to the synergistic effects between adjacent metallic centers. Therefore, it is essential to review the opportunities and challenges of MACs in the carbon neutrality field, offering potential guidance for future research.